PENDEKATAN AUTOETNOGRAFI DALAM PENELITIAN ARTISTIK: STUDI KASUS DAN IMPLIKASI METODOLOGIS - Peradantha, Ida Bagus Gede Surya (Jurnal Kajian Seni, 2024)
The primary aim of this research is to enhance understanding of autoethnographic perspectives in artistic research. It also seeks to explore the contributions, challenges, and potential of this approach in expanding creative knowledge. Certain artists may perceive the evaluation of their own artworks as excessively subjective, which may lead to doubts regarding the scientific rigor of the subsequent research. This study examines various autoethnographic models within artistic research and their application in previous studies. Employing a qualitative framework, this study utilizes a literature review approach. Content analysis was employed to extract data from relevant documents, while meta-synthesis was used for comprehensive analysis. This study uncovers that there are four distinct kinds of autoethnographic approaches: realistic, impressionistic, expressionistic, and conceptualistic. These models provide several frameworks that can be utilized for studies focused on artwork, practice, studio, and reflective experiences, particularly in relation to the subjective experiences of creators. This study discovered a theory of artistic experience that is strongly linked to the fusion of the artistic research model and the autoethnographic approach model. This research has profound implications for broadening art research approaches, enhancing comprehension of the creative process, promoting critical cultural analysis, producing novel theories of artist experience, and fostering future art and autoethnographic research.